Potential of Collagen as an Active Ingredient in Cosmetics - Denayu Pebrianti; Mikhael Ardi Kristiawan; Rima Hidayatul Qoiriyah; Siti Nur Kholisah; Aulia Hanin Fakhira; Laila Nur Azizah; Cindi Dia Rakhmawati; Muhammad Hilal Salim; Aviatus Solikhah; Rohana Ayu Pramesti; Rika Putri Septiawati; Melanny Ika Sulistyowati; Muh. Agus Syamsur Rijal (Berkala Ilmiah Kimia Farmasi, 2023)
Skin was the part of the outer body that was most often exposed to external factors, especially ultraviolet radiation. The skin had an important role in supporting the appearance so that it could affect human social life. Skin aging was a process of decreasing the body's physiological functions that could not be avoided. The aging process of the skin could be caused by a decrease in collagen density and replacement of essential structural proteins so that the skin loses its integrity and elasticity. Collagen was the most abundant protein in humans which could be found in bones, muscles, skin and tendons. Several studies had shown that damaged collagen fibers could be replaced by new fibers when collagen production was stimulated, which was why many cosmetic industries were competing to develop the use of collagen. Collagen had shown potential as an antioxidant, skin moisturizer, and anti-aging. Therefore, this article examined the benefits of collagen, especially in the cosmetic field. This article also discussed the sources of collagen with the best properties as active ingredients for skin care products. Keywords:  Collagen, Cosmetics, Antioxidants, Moisturizers, Anti-Aging